Exogenous 6-Benzyladenine Improved the Ear Differentiation of Waterlogged Summer Maize by Regulating the Metabolism of Hormone and Sugar - Hu, Juan; Ren, Baizhao; Chen, Yuhai; Liu, Peng; Zhao, Bin; Zhang, Jiwang (Frontiers in Plant Science, 2022)
Waterlogging is a major abiotic stress during the growth cycle of maize production in Huang-huai-hai plain of China, threatening food security. A wide range of studies suggests that the application of 6-benzyladenine (6-BA) can mitigate the waterlogging effects on crops. However, the mechanisms underlying this process remain unclear. In this study, application of 6-BA effectively increased the yield of summer maize was confirmed to be related with the hormone and sugar metabolism. At the florets differentiation stage, application of 6-BA increased the content of trans-zeatin (TZ, +59.3%) and salicylic acid (SA, +285.5%) of ears to induce the activity of invertase, thus establishing sink strength. During the phase of sexual organ formation, the TZ content of ear leaves, spike nodes, and ears was increased by 24.2%, 64.2%, and 46.1%, respectively, in W-B treatment, compared with that of W. Accordingly, the sugar metabolism of summer maize was also improved. Therefore, the structure of the spike node was improved, promoting the translocation of carbon assimilations towards the ears and the development of ears and filaments. Thus the number of fertilized florets, grain number, and yield were increased by the application of 6-BA.